Mechanical food properties and dental topography differentiate three populations of Lemur catta in southwest Madagascar. Issue 98 (September 2016) - Yamashita, Nayuta; Cuozzo, Frank P.; Sauther, Michelle L.; Fitzgerald, Emily; Riemenschneider, Andrea; Ungar, Peter S.
Abstract: Determining the proximate causes of tooth wear remains a major focus of dental study. Here we compare the diets of three ring-tailed lemur ( Lemur catta ) populations and examine how different dietary components may contribute to patterns of wear-related tooth shape. Casts were made from dental impressions collected between 2003 and 2010 from lemurs in the gallery and spiny/mixed forests of the Bezá Mahafaly Special Reserve (BMSR; Parcels 1 and 2) and the spiny/mixed forests of Tsimanampesotse National Park (TNP), Madagascar. Tooth shape variables (occlusal relief and slope, angularity) were analyzed using dental topographic analysis. Focal observations and food mechanical properties (FMPs: toughness, hardness, elastic modulus) were conducted and tested, respectively, during wet and dry seasons from 2008 to 2012. We found that FMPs correlate with patterns of dental topography in these three populations. Specifically, food toughness and elastic modulus correlate with the dental variables, but hardness does not. Average food toughness and elastic modulus, but not hardness, are highest in BMSR Parcel 2, followed by BMSR Parcel 1 and TNP. Occlusal relief and slope, which serve as proxies for tooth wear, show the greatest wear in Parcel 2 and the least in TNP. Angularity is also more pronounced in TNP. Further, dental topographic patterns correspond to reliance on Tamarindus indica (tamarind) fruit. Both BMSR populations consume tamarind at high frequencies in the dry season, but the fruits are rare at TNP and only occasionally consumed. Thus, high seasonal tamarind consumption and its mechanical values help explain the low dental relief and slope among BMSR lemurs. By investigating the ecology of a single widespread species across a variety of habitats, we have been able to link specific components of diet to patterns of dental topography in this species. This provides a context for interpreting wear-related tooth shape changes more generally, illustrating that populations can develop different dental wear patterns resulting from a mix of intrinsic factors (thin enamel) and local conditions (food properties, frequency of consumption).